Mesoporous biochar reshapes soil water dynamics under shallow groundwater: interactions with nitrogen management - Elbana, Maha; Gamal, Rania; El-Shirbeny, Mohammed A.; Rashad, Mohamed; Brouziyne, Youssef; Abou Hadid, Ayman F. (Frontiers in Soil Science, 2025)
Shallow groundwater tables influence nearly one-quarter of global croplands, yet the role of biochar in such hydropedological settings remains poorly understood. This study investigated how mesoporous biochar interacts with nitrogen fertilization to modify soil properties, water dynamics, and irrigation requirements in a clay loam soil of the Nile Delta, Egypt. A two-season field experiment using randomized complete block design tested biochar (35 t ha-1) combined with three nitrogen levels (100, 80, and 50% of the common farmer practice). Biochar significantly increased available N, Ca, and Mg and altered soil moisture profile: Instead of monotonic moisture increase typical of shallow groundwater conditions, an S-shaped distribution developed within the 0–30 cm layer. Drainage losses consistently declined when biochar was combined with moderate nitrogen input. Although crop yield and fruit quality responses were not statistically significant, the biochar-nitrogen combination reduced irrigation demand by ~82 m3 ha-1 yr-1 compared to conventional management. When scaled regionally under same environmental conditions, this strategy could save >80 million m3 of irrigation water annually in Egypt, assuming 100% irrigation efficiency. These findings show that mesoporous biochar can reshape root-zone water dynamics under shallow groundwater, offering a promising strategy to enhance water-use efficiency in water-scarce regions.